TEKNOLOGI TELEVISI DAN EKSISTENSI MANUSIA - Ari Abi Aufa (MIYAH : Jurnal Studi Islam, 2018)
Abstract: Since the very begining, industrial revolution had shaked and shaped modern people’s culture and created new cultures that never exist before. Positivistic  way of thinking on science had become basic requirement of scientific research that spring technological inventions related and unseparated with every side of human activities. Technological deter-minism which came along with television put this technological artefact into a new role that never meant before, a role that surpases the basic purpose on creating this ‘tool’. A man, unconsciously, is slaved by the technology, while he feels mastering it. This research tries to find the essence of technology, especially television, the essence that lies behind the material and use of it. Understanding the essence of the technology will open deeper understanding of human existence related with technology. This research shows that technology plays vital role in modern civilization and take deep control on human activities. This role endangered human existence who ignore their authentity and enjoyed of being inauthentic.Key words: Technology, Television, and Existence